Myocardial remodeling and arterial stiffness depending on aldosterone level in patients with chronic kidney disease and arterial hypertension - O. V. Kuryata; V. V. Semenov (Zaporozhye State Medical University, 2019)
The aim. To analyze the relationship between serum aldosterone levels and myocardial remodeling and changes in elastic properties of arteries in patients with chronic kidney disease (CKD) and hypertension (AH). Materials and methods. A cross-secitonal study of 44 patients (14 men and 30 women, aged 56.0 [52.0; 60.5] years) with CKD and AH who were treated with angiotensine-converting enzyme inhibitors or angiotensine receptor blockers at a stable dose for at least of 3 months was performed. Serum aldosterone levels, elastic properties of the arteries, and transthoracic echocardiography using a standard method were performed. Arterial stiffness was defined as a pulse wave velocity, which was calculated using equation proposed by Arterial Stiffness Society and was measured using a device BAT41-2. Results. In 8 patients (18.2 %) we detected serum aldosterone levels above 90 pg/ml. The proportion of female patients among patients with normal aldosterone levels was significantly higher (P = 0.03). Patients with elevated aldosterone levels had a 5-year higher median age and 10 ml/min lower glomerular filtration rate. Serum aldosterone levels correlated significantly with myocardial structural and functional parameters (left ventricle (LV) end-systolic and end-diastolic dimensions and volumes, LV myocardial mass and LV mass index, thickness of interventricular septum) in men and patients over 55 years of age. Women showed a weak correlation of aldosterone levels with systolic and diastolic blood pressure. Conclusions. An association was found between serum aldosterone levels above 90 pg/ml in patients with CKD and hypertension with dilatation of left ventricular and atrial cavities, and with left ventricular hypertrophy (by LV mass and mass index). This association was stronger for males and for patients aged >55 years. A correlation between aldosterone level and arterial stiffness (augmentation index on the brachial artery and aorta) has only been found in patients over 55 years of age.